2020
DOI: 10.3389/fphar.2020.00109
|View full text |Cite
|
Sign up to set email alerts
|

Toddalolactone Protects Lipopolysaccharide-Induced Sepsis and Attenuates Lipopolysaccharide-Induced Inflammatory Response by Modulating HMGB1-NF-κB Translocation

Abstract: Toddalolactone (TA-8) is a main compound isolated from Toddalia asiatica (L.) Lam., and its anti-inflammatory activity and anti-inflammatory mechanism are less studied. In the present study, we investigated the anti-inflammatory effects of TA-8. Our experimental results showed that TA-8 inhibited the production of pro-inflammatory cytokines by both lipopolysaccharide (LPS)-activated RAW 264.7 cells and septic mice. Moreover, TA-8 suppressed the NF-kB transcriptional activity, reduced the nuclear translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 42 publications
(39 reference statements)
1
40
0
Order By: Relevance
“…2&3), the present study cleared out that the liver enzymes (transaminases) were elevated greatly in the induction group and that may be attributed to the effect of Lipopolysaccharide (LPS) which stimulate the septic liver injury resulting in activation the transcription factor nuclear factor-kappa B (NF-κB) and leading to activation of many inflammatory genes, such as TNF-α and IL-1β [52,86]. NF-κB is one of the most important inflammatory cytokines, and know it is used as an indicator and biomarkers for inflammatory response in different diseases more over it become the target of many anti-inflammatory drug discovery programs .The administration of LPS in animal models induces the expression and release of NF-κB [52]. Most authors observed the NF-κB serum peak as early as 0.5 2 h after injection with LPS[8, 4Previous studies showed that decreasing the flow of liver blood through portal shunt down regulates the systemic levels of NF-πB [52]In rat model [52], the portal vein ligation decreased LPS-induced NF-κB [52].…”
Section: Impact Of G Oblongata On the Inflammatory Biomarkersmentioning
confidence: 63%
“…2&3), the present study cleared out that the liver enzymes (transaminases) were elevated greatly in the induction group and that may be attributed to the effect of Lipopolysaccharide (LPS) which stimulate the septic liver injury resulting in activation the transcription factor nuclear factor-kappa B (NF-κB) and leading to activation of many inflammatory genes, such as TNF-α and IL-1β [52,86]. NF-κB is one of the most important inflammatory cytokines, and know it is used as an indicator and biomarkers for inflammatory response in different diseases more over it become the target of many anti-inflammatory drug discovery programs .The administration of LPS in animal models induces the expression and release of NF-κB [52]. Most authors observed the NF-κB serum peak as early as 0.5 2 h after injection with LPS[8, 4Previous studies showed that decreasing the flow of liver blood through portal shunt down regulates the systemic levels of NF-πB [52]In rat model [52], the portal vein ligation decreased LPS-induced NF-κB [52].…”
Section: Impact Of G Oblongata On the Inflammatory Biomarkersmentioning
confidence: 63%
“… 8 Moreover, Ni et al. 28 concluded that the interception of NF-κB nuclear translocation and phosphorylation confers anti-inflammatory and immunosuppressive effects in LPS-induced sepsis. The overall influence of miR-410-3p on sepsis may also involve IL-6 and NF-κB to some extent, but the underlying mechanism in connection with TLR2 requires further investigation and should be addressed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Equal volume of 0.9% saline was intraperitoneally injected into the Veh group. The LPS+BV group received an intraperitoneal administration of bee venom (100 μg/kg body weight) 1 h before administration of LPS [ 15 , 16 ]. Honeybee ( Apis mellifera L.) colonies were maintained at the National Institute of Agricultural Science and Technology (Suwon, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Bee venom was collected in a sterile manner and purified by Chung Jin Biotech Co. (Ansan, Korea), as previously described [ 17 ]. The dose of LPS and bee venom was determined based on the results of previous studies [ 15 , 16 , 17 , 18 ]. All mice were sacrificed 24 h after LPS injection.…”
Section: Methodsmentioning
confidence: 99%